The reversal : a novel - Connelly, Michael, 1956- (Connelly, Michael, 1956- Lincoln lawyer novel., 2016)
Longtime defense attorney Mickey Haller never thought he would cross the aisle and work for the prosecution--until imprisoned child killer Jason Jessup is granted a retrial based on new DNA evidence. Convinced Jessup is guilty, Haller takes the case on the condition that he gets to choose his investigator, LAPD Detective Harry Bosch. But there's a serious political taint on the case, and Haller must face down a celebrity defense attorney who has already started trying it in the media. While Bosch searches the cold trail for the eyewitness who was the key to Jessup's original conviction, the convict is released on bail. Now Haller and Bosch fear the worst: This killer may have just gotten started--and the trial is a matter of life-and-death for everyone.